PEMAHAMAN HADIS TEKSTUAL DAN KONTEKSTUAL : (Kajian Pendekatan Teori Antropologi) - Ahmad Husein; Azhar Nasution (Al-Mu'tabar, 2025)
This article describes how to understand hadith textually and contextually, approaches that each have their own advantages and disadvantages. Getting stuck on one of these approaches will reduce the important aspects of each approach. Issues in society often touch on religious aspects, including the use of religious symbols as justification for the truth. Hadith is the second source in Islam, so it is imperative to examine every aspect of it. In understanding a hadith, researchers are inevitably caught up in several approaches, including textual and contextual. These two approaches have recently become a source of conflict in society. To examine this phenomenon, the author uses a qualitative method with anthropological theory in a contextual approach. The results of this study show that the contextual approach is more convincing in its application in the public sphere because this approach does not reduce the human aspects in approaching a hadith, which is in fact theological in nature. With an understanding of humans and their problems, alternative solutions can be sought to analyze current social issues, thereby bridging the various problems faced by humans. Interpreting hadiths with a contextual approach in the present day, when society has become more advanced, as has its artistic creativity, which has also been used as a form of creative economy that provides opportunities.